Void Avoidance in Underwater Acoustic Sensor Network Using Secure Opportunistic Energy Efficient Depth Routing Protocol - Battula, Ashok; Roslin, S. Emalda; Florin, W. (International journal of computer network and information security, 2023)
For starters, in UASN, distance between nodes as they move with water current, improved network's energy usage. The second problem with UASNs is void hole occurrence, which affects network performance. Nodes are unable to deliver data to the destination because there are no forwarder nodes (FNs) in the network. As a result, routing in UASNs aims to solve the previously mentioned issues in order to increase the network's lifespan. This research proposed novel technique in Void avoidance in underwater acoustic sensor network (UASN) with improving the energy efficiency of the network and analysing depth with security. In this proposed model, secure opportunistic energy efficient void avoidance protocol (Se_Opp_EE_VA) is used and the depth of the network has been analysed. By avoiding the vacuum zone and balancing network energy with depth analysis and security, the suggested effort extends the network lifetime. Routing techniques must be comprehensive enough to overcome all of these constraints as well as provide an energy-efficient routing that avoids empty zones while also extending network lifetime. The depth factor is used in depth-based algorithms proposed in recent decades to assess the path from sender to sink. They reduce information replication by using the holding time calculation. 81% of QoS, 92% of PDR, 96% of energy efficiency, Network lifetime attained by Proposed Se_Opp_EE_VA is 94%, and 50% of end to end delay have all improved as a result of the simulation.